2014
DOI: 10.1016/j.sajb.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation of seed germination requirements of the threatened Mediterranean species Malcolmia littorea (Brassicaceae) and implications for its reintroduction

Abstract: Malcolmia littorea (Brassicaceae) is a threatened species growing in the coastal sandy dunes of the westMediterranean basin. In this study, the seed germination and seedling emergence requirements of this species were investigated in the only remaining native population in Italy. The highest germination percentage was achieved in darkness with scoring under safe green light at 5-10°C. Seedling emergence was highest when seeds were buried between 1 and 10 mm in depth. The results suggest that germination and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
16
1
2
Order By: Relevance
“…The role of the maternal environment during seed development, as a factor that can influence germination behaviour of M. littorea , has already been reported (De Vitis et al . ). It was shown that after one generation of ex situ plant cultivation under different conditions than the natural environment, seed germination performance was altered, compared to the seeds produced by the native population (De Vitis et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The role of the maternal environment during seed development, as a factor that can influence germination behaviour of M. littorea , has already been reported (De Vitis et al . ). It was shown that after one generation of ex situ plant cultivation under different conditions than the natural environment, seed germination performance was altered, compared to the seeds produced by the native population (De Vitis et al .…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that after one generation of ex situ plant cultivation under different conditions than the natural environment, seed germination performance was altered, compared to the seeds produced by the native population (De Vitis et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a result, restoration measures depending on seedling recruitment are sensitive to environmental maternal effects (Bischoff & Müller‐Schärer ; De Vitis et al . ).…”
Section: Introductionmentioning
confidence: 97%